Retrospective review of trends in assaults and seclusion at an acute psychiatric ward over a 5‐year period. Issue 8 (19th September 2012) - Luckhoff, M.; Jordaan, E.; Swart, Y.; Cloete, K. J.; Koen, L.; Niehaus, D. J. H.
<x xml:space="preserve">Abstract</x> Accessible summary Research on trends in assaults and seclusion over time in developing countries such as South Africa is scant. Here, we assessed trends in assaults and seclusion, stratified by gender, at the acute admission wards in one psychiatric facility over a 5‐year period. The results of this study show that continuous monitoring of assaults and seclusions is important to improve quality of care. Abstract In developing countries such as South Africa, not much is known about the prevalence of assaults and seclusion occurring in mental health wards over time. Here, we describe a 5‐year trend in assaults and seclusions, stratified by gender, at Stikland Hospital, South Africa. A retrospective review of clinical records of patients admitted to the acute psychiatric admission wards at Stikland and involved in assault and secluded was undertaken between 1 January 2005 and 31 December 2010. Data on the number of patient and staff assaults as well as seclusions, gender, age, marital status, level of education, level of income, duration of hospital admission and primary psychiatric diagnosis were collected. Significantly (P < 0.01) more men than women engaged in patient assaults, while significantly (P < 0.01) more men were secluded than women. On a monthly basis, the number of gender‐stratified patient assaults and seclusions significantly increased (P < 0.01) throughout the study period. In conclusion, we show here that gender had a significant effect on both patient assault and seclusion numbers, which increased towards the end of the study period. Monitoring of these events is therefore important to continuously improve quality of care.